A new record of Portulaca (Portulacaceae) to La Réunion Island, Portulaca. cf. pilosa L.: native or recently (re-)introduced?. Issue 2 (3rd April 2018) - Augros, Stéphane; Hoareau, Dominique; Baider, Cláudia
Abstract: Two species of Portulaca were currently reported from La Réunion Island, the native P. oleracea and the introduced P. quadrifida . A third species was presumed but never confirmed, P. pilosa . We recently found a population of P. cf. pilosa in a restricted area in the southwestern part of La Réunion, exclusively growing on tiles of tuff, a very singular and restricted habitat that also shelters some native and rare species, but is largely surrounded by alien vegetation. Given the cosmopolitan distribution of P. pilosa in warm regions, we suggest that the species could be alien. However, based on the wide infrageneric taxonomic resolution problems of Portulaca, coupled with the species' alleged past records for the Mascarene and its presumed rarity, we call for more in-depth studies to assess the true origin and ecological significance of the species.